Perlindungan hukum bagi konsumen marketplace terhadap pencantuman berat bersih dalam produk makanan kemasan - Nesiaindo Aira Putih Merah; Sylvana Murni Deborah Hutabarat (Jurnal Cakrawala Hukum, 2022)
This study aims to determine the protection for consumers and the responsibilities of business actors in packaged food products in the marketplace according to Indonesian legislation. In its implementation, it uses normative juridical methods, analyzes descriptive data with a qualitative approach, and examines primary data and secondary data. Research shows that the protection regulations for marketplace consumers against the inclusion of net weight in packaged food products have been regulated in Indonesian legislation. Technological developments make the buying and selling process easier. Through the marketplace, a website or application is used as a place for buying and selling from several vendors. There are various packaged products traded, which is one of the provisions stating that packaged food products are eligible for distribution based on quality, health, content, and net weight. Various kinds of laws and regulations become references in regulating the distribution of packaged food in the marketplace. Consumer protection questions legal protection, so as a law that has rules regarding protection to consumers and the way business actors are responsible for defending their rights and carrying out their obligations. Article 22 of Law Number 2 of 1981 concerning Legal Metrology regulates the reasons for the inclusion of net weight that should be included in packaged food products. The inclusion of net weight is very necessary to be included in the actual packaging of food products.How to cite item: Putih Merah, N., Hutabarat, S. (2022). Perlindungan hukum bagi konsumen marketplace terhadap pencantuman berat bersih dalam produk makanan kemasan. Jurnal Cakrawala Hukum, 13(1), 58-67. DOI:https://doi.org/10.26905/idjch.v13i1.5333.